(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study assessed soil degradation and nutrient dynamics in seasonal wetland ecosystems under continuous rice cultivation in Atani and Odekpe, Anambra State, Nigeria. Soil samples were collected from rice fields and adjacent 5-year fallow (control) soils at two depths (0-15cm and 15-30 cm), and analyzed for selected soil physicochemical properties. Results showed high bulk density in the rice field (2.01 Mg/m3 at Atani), reduced organic carbon (1.07% at 15 30 cm in Odekpe), and high cadmium levels (0.38 mg/kg at 15-30 cm in Odekpe rice field). The soils showed moderate acidity across locations with pH values ranging from 5,45 to 6.00. The soil degradation index (SDI), computed as the weighted sum of normalized scores for eight degradation-sensitive parameters, ranged from 0.231 (Odekpe control at 15-30 cm depth) to 0.438 (Odekpe control at 0-15 cm depth). Rice fields showed inconsistent SDI values with depth, while control soils consistently had lower degradation at 15-30 cm depth. The findings showed that long-term rice cultivation, through agrochemicals use and tillage, significantly alters soil properties and increases degradation.